E-Marketing: Challenges And Opportunities For The Marketers - Deshwal, Dr. Parul (International Journal of Scientific Research and Management (IJSRM), 2015)
In the era of globalization internet plays a vital role in all spheres of life and industries. Internet is very famous nowadays for satisfying people with various services related to various different fields. It is a versatile facility which can help you in completing many tasks easily and conveniently with few clicks. EMarketing, which is also called internet marketing, involves use of interactive, virtual spaces for the sake of promoting and selling goods and services E-marketing is growing at a dramatic pace and is impacting customer and market behaviours. This has forced firms to start incorporating e-marketing as the main form of marketing and try to meet their targeted customers’ needs to the satisfaction. This paper investigates and states about e-marketing, what the current trend of the marketing field is and what are the future of emarketing. The paper has found and concluded that e-marketing is the future as it has been positively affected by the current technological change which has made the use of smart phones and gadgets a necessity